Modern cartography as a science :Powerpoint - Kraak, M.J. (University of Twente, 2020)
This lecture presents: Maps tell stories; Maps to present; Cartography; Data characteristics; Data characteristics; Exploratory tools; Beyond Cartography: Visual Analytics; Geovisual analytics; Detect the expected and discover the unknown.